(untitled) (Research, Society and Development, 2022)
The degradation process of coatings can be associated with several aspects. Among them, there is often the action of environmental factors, which vary according to the location and orientation of a building’s facade. Hereupon, investigating the relationship between the appearance of pathological manifestations and the action of the weather is essential to verify the current state and progress of the degradation which the buildings are subjected. The present work aims to evaluate the occurrence and incidence of anomalies, identifying patterns on the facades, establishing a relationship with the effects of these agents. The Degradation Measurement Method was used, corresponding to the inspection of buildings in use. The methodology is applied in the Post-Graduation in Letters Building of the Federal University of Pará, located in the neighborhood of Guamá, in Belém - PA. Moisture staining corresponds to the most frequent and serious anomaly on continuous walls, mainly on the facade facing east, where there is the greatest exposure to environmental agents responsible for this type of pathological manifestation, mainly due to the high incidence of rain directed at the facade.